Pemberdayaan Ibu Rumah Tangga dalam Meningkatkan Pendapatan Keluarga Melalui Produksi Ekonomi Kreatif (Studi Pengolahan Pelepah Pisang Pada Mega Souvenir Desa Harapan Makmur Kabupaten Bengkulu Tengah) - Khairiah Elwardah (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2020)
This study aims to describe how the process of empowering housewives in Harapan Makmur Village, Central Bengkulu Regency, which has been successfully carried out by Mega Souvenir since 2012 to 2017 through the creative economy, namely processing banana fronds and how housewives' income is due to empowering the stages that must be passed. The researcher used a qualitative approach by observing, interviewing, and documenting as a data collection tool and Miles and Huberman's data analysis techniques which emphasize 3 aspects in processing data obtained in the field. The results showed that the stages of empowerment carried out by Mega Souvenir succeeded in making 10 housewives able to become independent individuals by dividing time between discipline in work and household care. These housewives also have an income through the creative economy in the form of processed banana fronds into high-value items. So that income can support the family economy which has been relying on income from her husband. Even the income of 4 people from 6 housewives in this time period is commensurate with the UMR set by the Bengkulu provincial government.